PENGARUH PENGGUNAAN SMARTPHONE TERHADAP PRESTASI AKADEMIK MAHASISWA PRODI PPKn FKIP UNIVERSITAS RIAU - Oktaviani, Denti; Hambali, Hambali; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by a phenomenon that arises based onobservations during the lecture period before using the network, there are still studentswho keep in touch with their smartphones because they are bored, bored, sleepy andless interesting learning materials. Then based on the results of the pre-surveyconducted by researchers, it was found that students could use their smartphones inabout ± 20 hours a day and even students could use their smartphones for up to 24hours a day because smartphones have become a necessity in everyday life. This studyaims to determine the effect of smartphone use on academic achievement of students inthe Pancasila and Citizenship Study Program, Faculty of Teacher Training andEducation, University of Riau. The population in this study were students of the PPKnFKIP Riau University Study Program with a sample of 56 students. The instruments inthis study were observation, questionnaires, interviews and documentation. Thisresearch method uses quantitative descriptive analysis, the data is analyzed usingsimple linear regression. So, the hypothesis in this study is accepted, where the use ofsmartphones and their effect on academic achievement of students of the PPKn FKIPRiau University study program shows excellent results. Because based on thecalculation, it is known that the coefficient of determination (R square) is 0.464, whichimplies that the effect of the independent variable (smartphone use) on the dependentvariable (academic achievement) is 68.1%.Key Words: Smartphone Usage, Influence and Academic Achievement